Effects of antioxidant supplementation on oxidative stress balance in young footballers- a randomized double-blind trial - Błażej Stankiewicz; Mirosława Cieślicka; Sławomir Kujawski; Elżbieta Piskorska; Tomasz Kowalik; Justyna Korycka; Anna Skarpańska-Stejnborn (Taylor & Francis Group, 2021)
Background Intensive physical exercise that competitive sports athletes participate in can negatively affect their pro-oxidative-antioxidant balance. Compounds with high antioxidant potential, such as those present in chokeberry (Aronia melanocarpa), can prevent these adverse changes. We here investigated the effect of antioxidant supplementation on oxidative stress balance in young footballers. Methods The study was designed as a double-blind randomized trial. Diet of a group of young football players (male; n = 20; mean age, 15.8 years-old) was supplemented with 200 ml of chokeberry juice per day, for 7 weeks. The players were randomly assigned to the experimental (supplemented, FP-S; n = 12) and control (placebo, FB-C; n = 8) groups. Before and after the supplementation period, the participants performed a beep test. Venous blood was sampled for serum analysis before, immediately after, 3 h, and 24 h after the beep test. Serum levels of thiobarbituric acid reactive products, 8-hydroxy-2'-deoxyguanosine, total antioxidant capacity, iron, hepcidin, ferritin, myoglobin, and albumin, and morphological blood parameters (red blood cells, (RBC), haemoglobin (HGB), haematocrit (HCT) mean corpuscular volume (MCV) mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), and lactic acid) were determined. Results Chokeberry juice supplementation did not significantly affect the outcome of the beep test. The supplementation did not significantly affect any of the morphological, biochemical, or performance parameters analysed. Conclusions Chokeberry juice supplementation did not affect the measured parameters in the studied population, which may indicate insufficient antioxidant capacity of the juice.